225k views
0 votes
8(10−6q)+3(−7q−2) simplify to an equivalent expression

2 Answers

4 votes

Answer:

Explanation:

80 - 48q - 21q - 6

-48q - 21q + 80 - 6

-69q + 74

User TylerW
by
4.8k points
1 vote


\bold \red{ \: Ur \: Query}

⟹ 8(10−6q)+3(−7q−2) simplify to an equivalent expression


\bold \red{ \: Answer}

⟹ 74 - 69q


\bold \red { \: Step \: by \: Step \: Explanation}

⟹ 8(10−6q)+3(−7q−2)

⟹ 80-48q - 21q-6

⟹ 74 - 69q

  • Or

⟹ -69q + 74


\huge \bold \blue {Hope \: It \: Helps \: u}

User Fredrik Frodlund
by
5.5k points